Dealing with diversity—blind and visually impaired ski guiding in physical education teacher education - Sträter, Helena; Heidrich, Franziska; Steineck, Iris; Lobert, Ann-Kathrin; Pfitzner, Michael (Frontiers in Sports and Active Living, 2025)
A positive attitude towards diversity seems to be crucial for successful inclusion in physical education (PE). However, some previous studies point to counterproductive attitudes of PE teachers in general and towards children with blindness or visual impairments (BVI) in particular. The present study examines how a seminar focusing on BVI ski guiding influences PE teacher education (PETE) students’ attitudes towards diversity. The seminar includes the experience of guiding a fellow student, who in turn experiences simulated BVI skiing. Subsequently, students have the option to participate in a project guiding people with actual BVI. To explore the influence of the seminar on students’ attitudes, a qualitative interview study was conducted. The findings suggest that the positive experiences go beyond the specific activity of BVI ski guiding. The seminar appears to foster the development of favourable attitudes towards diversity in general. Participants noted reduced feelings of uncertainty and an increase in self-efficacy. Nevertheless, some uncertainties persist due to the unique nature of each person and situation. The results demonstrate the benefits of purposefully designed PETE seminars that enable students to interact with people with disabilities and in this case especially those with BVI. Participation in such teaching-learning concepts entails embracing new experiences, encountering different learning environments, and overall, engaging in intense and demanding work on one's own (professional) biography, which could lead to a deeper understanding of people's needs and an open-minded attitude more generally.